Implementation of Interactive Storybook Media to Improve Reading Comprehension Among Third-Grade Madrasah Ibtidaiyah Students - Shindi Pratiwi; Boby Syefrinando; Ika Panggih Wahyuningtyas (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study was motivated by the low reading comprehension ability of third-grade students at MIS Al-Munawwarah, which was caused by the lack of engaging learning media and students’ low interest in reading. The purpose of this study was to improve students’ reading comprehension through the implementation of interactive storybook media in Indonesian language learning. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects of this study were 30 third-grade students at MIS Al-Munawwarah. Data collection techniques included observation, interviews, tests, and documentation. Data were analyzed using both qualitative and quantitative descriptive approaches. The results of the study showed that the use of interactive storybook media was able to improve students’ reading comprehension. This improvement was indicated by the increase in students’ learning outcomes in each cycle, as well as the enhancement of students’ participation, interest, and motivation during the learning process. In addition, the use of this media made the learning process more engaging and interactive. In conclusion, interactive storybook media is effective in improving the reading comprehension of third-grade students in Indonesian language learning at MIS Al-Munawwarah.